Sexual Assault, Posttraumatic Stress, Alcohol Use, and Suicidality Among Diverse College Students - Gilmore, Amanda K. (Journal of interpersonal violence, 2023)
Suicide is the second leading cause of death among college-aged populations. This study examined the association of demographics (sexual orientation, gender identity, age, and race), sexual assault, posttraumatic stress symptoms (PTSS), and alcohol use with suicidality, current urge to self-harm, and current suicidal intent among a diverse sample of college students (n = 2,160) from two universities. Over half of participants reported any suicidality (63.5%), 12% reported current urge to harm themselves, and 5% reported current suicidal intent. A linear regression indicated that participants who identified as a sexual minority, gender minority, consumed more drinks per week, and had more severe PTSS reported higher levels of suicidality. University also was associated with suicidality. A negative binomial regression demonstrated that participants who identified as a sexual minority and had more severe PTSS had more current urge to harm themselves. Further, a negative binomial regression demonstrated that first-generation college students, students with more severe sexual assault histories, and students with more severe PTSS had higher current suicidal intent. Findings suggest that risk factors may differ for college students’ general suicidality, self-harm urges, and suicidal intent, suggesting that these may be separate constructs. More comprehensive models, incorporating multiple risk factors and multiple ways of assessing suicidality, are needed to better understand the range of college student suicidal behavior and risks.